(untitled) (Fourth World Journal, 2025)
Indigenous students in Canada do not graduate from secondary school at the same rate as their non-Indigenous peers. We argue in this article that the lower graduation rate is due to the many structural oppressions that Indigenous people experience. The authors concentrate on four large-scale oppressions that commonly face Indigenous students: poverty, suppression of their identities, racism and gender violence. Indigenous worldviews, perspectives and realities are at variance with the country’s dominant educational, economic and political institutions and negatively impact the self-esteem of Indigenous students. As well, their sociocultural identities are distinct, and undermined by the stereotypes and specific attributes designated to them. In order to counter these negative conditions and cultivate minopimaatisiiwin which is the Anishinaawpe concept of “living well” and “well-being”, we recognize a self-determination framework as essential to Indigenous education. A self-determination framework serves to strengthen Indigenous students’ identities to protect against dominant oppressions, foster resilience, and motivate younger generations towards improved educational outcomes.